Hubungan antara Self-Ffficacy dan Prokrastanasi Akademik pada Siswa SMA - Millenia Syadza Afra; Naharus Surur; Ma'rifatin Indah Kholili (Universitas Sebelas Maret, 2022)
This study aimed to (1) to identify levels of self-efficacy of 10th-grade students of high school students, (2) identify academic procrastination of 10th-grade students of SMA Batik 2 Surakarta, and (3) identify the relationship between the two variables among 10th-grade students . This quantitative, correlational study involved 167 10th-grade students as the population. Participants were recruited using a simple random sampling technique with the Slovin formula as a determinant of the number of samples, 118. Techniques used in data collection are distributing self-efficacy scales and academic procrastination scales. The instrument validity was confirmed using expert and construct validity, while its reliability was tested using Cronbach’s alpha with SPSS 26. The data were analyzed using descriptive and inferential analysis techniques to see the self-efficacy and academic procrastination levels and test the proposed hypotheses. The descriptive analysis result showed that most 10th-grade students (n=82) have a moderate level of self-efficacy (i.e., 69.5%), and most of them (n=84) also have an average level of academic procrastination (71.2%). The hypothesis test result indicates that self-efficacy is negatively and significantly associated with academic procrastination, as shown by a coefficient of -0.791. Suggestions for further research are to conduct experimental research to increase self-efficacy and reduce academic procrastination.